Desa Tanggap Budaya: Penguatan Tradisi Religi bagi Masyarakat di Desa Bongo Kecamatan Batudaa Pantai - Sayama Malabar; Zilfa A Bagtayan; Jafar Lantowa (Univeristas Negeri Gorontalo, 2022)
The problem that occurs in Bongo Village is the presence of outside culture that enters so that it affects the attitude of religiosity and activities in the village. This is because of the tourism potential that impacts the entry of foreign tourists so that it can have an impact on the local community. This problem is actually an opportunity to introduce local traditions to foreign tourists by re-activating youth organizations to carry out cultural-based creative activities in attracting tourists so that it helps in improving the economy in Bongo village. In responding to these problems, it is necessary to develop the potential of Bongo Village as a Religious Tourism Village. One of the potentials that can be developed is the cultural potential inherent in the village from generation to generation, both daily activities, arts, culinary, livelihoods, crafts and others. This can be the basis for forming a concept of rural tourism based on the culture of the area, which of course can be an attraction for tourists, both domestic and foreign tourists. Therefore, through the Village Thematic Community Service Program, the Lecturer at the State University of Gorontalo offered a collaboration with a partner, namely Bongo Village, Batudaa Beach District, Gorontalo Regency, Gorontalo Province. Empowerment activities are in the form of structuring tourist facilities, socializing the strengthening of local community religious traditions, and planning Bongo Village to become a Religious Tourism Village with the concept of Halal Tourism. In line with the problems found, the expected outcomes of this activity are (1) increased public awareness in maintaining religious traditions (2) the availability of tourism facilities based on local culture, (3) the creation of an orderly, mutual cooperation, and community life. willing to sacrifice for the achievement of the SDGs targets. (4) the realization of the involvement of the provincial government, especially village officials in paying attention to the facilities and availability of facilities in the development of religious tourism villages